Pola Komunikasi Public Relation Benings Clinic Pekanbaru Dengan Brand Ambasador - Fitri, Amelia; Moekahar, Fatmawati; Pratiwi, Yuly Rahmi (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2023)
The increasing development of technology today makes the flow of communication that occurs in the digital era increasingly faster, practical and efficient. Communication is more often done in cyberspace than communicating in the real world. One form of communication in the digital era that is quite well known is online and free platform-based messenger apps, namely WhatsApp messenger. For example, Benings Clinic public relations communicates using WhatsApp messenger to schedule uploads of promotions that are currently in effect at Benings Clinic. Benings Clinic uses brand ambassadors as product representatives and makes advertising appeals and testimonials emotional. The method used in this research is qualitative, with data collection techniques namely observation, interviews and documentation. The conclusion of the research is that the organizational communication pattern in PR Benings Clinic uses a wheel communication pattern where PR Benings Clinic is the focus of attention. Benings Clinic PR can communicate with all brand ambassadors, but each brand ambassador can only communicate with Benings Clinic PR and cannot interact with fellow brand ambassadors, because the focus is only Benings Clinic PR.